Asymptotic behavior of unbounded solutions of essentially nonlinear second-order differential equations. II - Evtukhov, V. M.; Kas'yanova, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We establish asymptotic representations for one class of unbounded solutions of second-order differential equations whose right-hand sides contain a sum of terms with nonlinearities of a more general form than nonlinearities of the Emden-Fowler type.